Implementation of Government Accounting System in Analyzing Factors Affecting Local Revenue of Jambi City. - Efrina, Liona; Irawan, Deki; Veronica, Deka; Tanjung, Ferri Saputra; Sari, Deby Anggun (Jurnal Smart: Sosial Ekonomi Kerakyatan, 2023)
This research is entitled Analysis of Factors that Influence Original Regional Income in Jambi City. In line with the implementation of the fiscal decentralization policy that has been implemented, increasing local original income revenue has become an important activity for the region in the context of financing routine expenditure and development in the region. In accordance with Law Number 25 of 1999, the fiscal decentralization policy for regions is expressed in the form of financial balance between the central and regional governments, where original regional income becomes one part of regional revenue. Apart from general allocation funds and special allocation funds, regional revenues from local original income are one of the main supporting factors in financing routine regional expenditure and determining success in implementing development programs. (Rusdin, 2004) The objectives of this research are as follows: (a) Know and analyze the development of local original income in Jambi City for the 1998-2021 period. (b) Know and analyze the factors that influence local revenue in Jambi City for the 1998-2021 period.The results of this research are 1) Per capita income in Jambi City has increased every year along with the increase in per capita income, so regional original income in Jambi City has also increased. The higher a person's income, the higher a person's ability to pay various levies set by the Government. Therefore, increasing per capita income will increase Jambi City's local revenue. 2) Based on the results of research on tax effort variables, per capita income and decentralization policies have a positiveand significant effect on Jambi City's original regional income, both simultaneously and partially.